2014
DOI: 10.1002/ep.12003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wood particle size and different process variables on the performance of steam‐oxygen blown circulating fluidized‐bed gasifier

Abstract: Pressurized circulating fluidized‐bed gasification by steam‐oxygen has been developed at VTT for syngas applications. In this process, wood feedstocks are first converted into raw gasification gas, which is then filtered at about 600°C before catalytic reforming of tars and hydrocarbon gases. This article presents results of the gasification and gas filtration tests carried out with wood pellets, crushed pellets, bark, and crushed forest residues. The effects of operating pressure, bed material used, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 7 publications
2
24
1
1
Order By: Relevance
“…The wet biomass feedstock is first dried from its initial moisture of 50 wt% to 15 wt% in a belt dryer operated with hot water recovered from the gasification plant. The dried chips are pressurised with lock-hoppers to 0.4 MPa and fed to a circulating fluidised-bed gasification reactor operating at 850 C. The gasifier is fluidised with equal amounts of steam and oxygen and used to convert wood chips into a raw product gas containing CO, H 2 , CO 2 , H 2 O, CH 4 and small amount of higher hydrocarbons and tars [32]. Before filtration, the gas is cooled 3 down to 550 C to condense alkali metals and to avoid blinding of the filter elements during dust removal [33].…”
Section: 1mentioning
confidence: 99%
“…The wet biomass feedstock is first dried from its initial moisture of 50 wt% to 15 wt% in a belt dryer operated with hot water recovered from the gasification plant. The dried chips are pressurised with lock-hoppers to 0.4 MPa and fed to a circulating fluidised-bed gasification reactor operating at 850 C. The gasifier is fluidised with equal amounts of steam and oxygen and used to convert wood chips into a raw product gas containing CO, H 2 , CO 2 , H 2 O, CH 4 and small amount of higher hydrocarbons and tars [32]. Before filtration, the gas is cooled 3 down to 550 C to condense alkali metals and to avoid blinding of the filter elements during dust removal [33].…”
Section: 1mentioning
confidence: 99%
“…In these studies we observed that CFB gasification is a stable and easily controlled process when the gasifier is operated at pressures up to 0.4 MPa, whereas operation above 0.5 MPa is challenging due to overheating of the bottom part of the gasifier bed, resulting in ash sintering problems. At lower gasification pressures, the bed material calcium as well as the inherent wood calcium is in the form of CaO, which has many positive effects on gasification as discussed in more detail in [11,16]. At higher pressures calcium is in the form of CaCO 3 , which does not have similar positive effects on tar decomposition and ash chemistry.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous study [16] focused on the initial development of the process concept and described the effects of the gasifier operating pressure, used bed material and other main gasifier operating variables on the gasifier performance. The main focus was on the gasifier operation, whereas the performance of the filter unit and the reformer was not yet studied in detail.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations